Elevated 12,13-diHOME level in maternal and umbilical cord blood complicated with preeclampsia - Yoshida, Tomohiro; Kitada, Kohei; Nakai, Kensaku; Uemura, Ryo; Kurihara, Yasushi; Tahara, Mie; Hamuro, Akihiro; Nakano, Akemi; Misugi, Takuya; Tachibana, Daisuke (Frontiers in Endocrinology, 2024)
Background Preeclampsia (PE) is a condition in pregnancy characterized by hypertension and proteinuria, thus leading to severe complications for both mother and fetus, including fetal growth restriction (FGR). However, there are still unclear aspects regarding the pathogenesis, prevention, and treatments. This study aimed to elucidate the characteristics of lipid metabolism in maternal and umbilical cord plasma complicated with PE using liquid chromatography-mass spectrometry (LC-MS). Method The study included singleton pregnant women at Osaka Metropolitan University Hospital from March 2023 to February 2024. PE was diagnosed based on new-onset hypertension after 20 weeks of gestation and other symptoms such as proteinuria and organ dysfunction. FGR was defined by ultrasound measurements below -1.5 standard deviation (SD). Plasma samples were collected from maternal and umbilical cord blood within 24 hours before delivery. Lipid metabolites were comprehensively analyzed using LC-MS, and the lipokine 12,13-diHOME, identified as elevated in the comprehensive analysis, was quantified. Immunohistochemistry was conducted on placental samples to assess soluble epoxide hydrolase (sEH) expression. Results The study involved 31 participants, with 20 in the control group and 11 in the PE group. A comprehensive analysis of maternal plasma samples identified a significant increase in 12,13-diHOME levels in the PE group compared to the control group. Quantification of 12,13-diHOME showed a significant increase in maternal plasma, umbilical venous plasma, and umbilical arterial plasma in the PE group compared to the control group (p = 0.007, p = 0.008, p = 0.005). PE with FGR showed significantly higher 12,13-diHOME concentrations in the umbilical arterial/venous ratio compared to the PE without FGR group (p = 0.03). Negative correlations were observed between 12,13-diHOME levels and birth weight in the PE group. Immunohistochemistry did not show significant differences in the sEH expression between the groups. Conclusion This study demonstrated that 12,13-diHOME levels were significantly elevated in maternal and umbilical cord blood in PE patients, particularly in PE with FGR. Elevated 12,13-diHOME may reflect the progression of placental ischemia due to PE pathogenesis. This lipid metabolite could serve as a marker for the severity of preeclampsia, thus providing new insights into perinatal lipidomics and the potential role of 12,13-diHOME in PE.